If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x+18=x-5
We move all terms to the left:
7x+18-(x-5)=0
We get rid of parentheses
7x-x+5+18=0
We add all the numbers together, and all the variables
6x+23=0
We move all terms containing x to the left, all other terms to the right
6x=-23
x=-23/6
x=-3+5/6
| 8/20=6/a | | -9(f+16)=45 | | 3*(2x+4)=60 | | –4d=8−6d | | 49=7(n-83) | | 3×(2x+4)=60 | | x+4x=9+11 | | p•3=18 | | s/4-24=33 | | 2x(4x-1)=50 | | 2x(4x-1)=50+ | | x.15+6x=45+8 | | 5(w+4)=75 | | 6x–8=4 | | 10s+5=65 | | 2(v-83)=20 | | k(-7)=10-7−19 | | 3c=1/72 | | j/7+73=79 | | 10−5v=–10−3v | | (h)35=50-35/5 | | –6p+11=–7p | | 5x+20°=2x-80° | | 3/4=x/80 | | Z^2-5x=0 | | -n-12n=0 | | b+40/3=2 | | -t+2t=0 | | -5x-8(7x+1)=-8 | | A=3b=4 | | A=3b=-4 | | 4(t-69)=80 |